PKM Penerapan Terpadu (PANDU) Manajemen Tata Laksana Obat Diare Pada Masyarakat - Rulia Meilina; Raudhatun Nuzul ZA; Ulfa Husna Dhirah (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of community service activities: (1) to provide personal and group education to the community; (2) to provide training on how to process and use traditional medicine from wealth starfruit leaves; (3) to establish a forum for health services in Lambada Lhok Village, Baitussalam District in PANDU. The methods used include surveys of activity locations, socialization of diarrhea management and training on traditional medicine processing, formation of PANDU, and evaluation of activities. The results achieved in this activity were the formation of the PANDU for Management of Diarrhea Drug Management in the Community in Lambada Lhok Village, Baitussalam District and the existence of a public understanding of how to process and use diarrhea medicine from Averrhoa bilimbi leaves for self-medication.